Design of a Novel Synbiotic Formulation to Optimize Gut-derived Phenolic Acid Mediated Gut-brain Axis Signals for the Treatment of Stress-induced Depression and Anxiety (OR23-03-19). (13th June 2019) - Westfall, Susan; Pasinetti, Giulio
Abstract: Objectives: Synbiotics, the combination of probiotics and prebiotics, may optimize the production of polyphenolic metabolites, and act as therapeutic agents for inflammation-induced depression. Recent evidence suggests that dysregulated immune activity increases susceptibility to depression and that bioactive polyphenolic metabolites can effectively reduce that inflammation. The problem remains that bioactive metabolite production is dependent on the gut microbiota, leading to significant interpersonal variation in the metabolites' therapeutic efficacy. The hypothesis of the study is that the synbiotic will standardize production and bioavailability of bioactive metabolites capable of suppressing innate immune biological signatures of depression. Methods: To standardize the production of bioactive metabolites, the synbiotic will be designed in an innovative in vitro model of the human gastrointestinal tract using a multivariate regression algorithm to predict which probiotic formulation produces the most effective bioactive metabolites. Following in vivo bioavailability and toxicity testing, the synbiotic's therapeutic efficacy was tested in a chronic unpredictable stress (CUS) mouse model of depression by measuring specific behaviors and changes to the gut microbiota populations. These changes were correlated to biological markers of depression modulated by the synbiotic-derived metabolites including neurobiological markers of depression and variations in innate immune markers, including interleukin-1β (IL-1β). Results: In this study, we show that a synbiotic combining a dietary polyphenolic preparation with L. plantarum and B. longum can potentiate the reduction in anxiety and depression in male mice subjected to a 28 day CUS protocol, as compared to polyphenolic treatment alone. Interestingly, we found that the synbiotic may mediate microglia inflammasome activation. This finding was reflected by inhibition of NLRP3-mediated generation of IL-1β in microglia. Conclusions: Collectively, these results support the potential role of a synbiotic in the potentiation of attenuation of psychological impairment in a model of depression through mechanisms that involved innate immune NLRP3 inflammation mediation in microglia. Funding Sources: This project was funding a P50 CARBON Center grant from the NCCIH/ODS (Pasinetti, PD/PI).